TRADISI MA`AWUO DANAU BAKUOK DIKECAMATAN TAMBANG KABUPATEN KAMPAR - Wahyu Nurcahyani; Ridwan Melay; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Ma`awuo Bakuok lake is tradition catching fish using net instruments is done besed on deliberation consensus. This tradition is a tradition of ancestors that have existed for hhundreds of years that continue to be maintained and preserved to this day. The purpose of this study are, 1) To know the history of tradition Ma`awuo Bakuok Lake in Tambang distrik of Kampar Regency, 2) To know the factors that encourage pople in doing tradition Ma`awuo Bakuok Lake in Tambang distrik of Kampar Regency, 3) To know the custom rules and the implementation of witnesses in tradition Ma`awuo Bakuok Lake in Tambang distrik of Kampar Regency, 4) To know the process of implementation of tradition Ma`awuo Bakuok Lake in Tambang distrik of Kampar Regency, 5) To know what values are contained in tradition Ma`awuo Bakuok Lake in Tambang distrik of Kampar Regency. The metodh used of is stady is qualitative method. Data obtained from the interview then analyzed by using the language itself. Location of this stady in Tambang district of Kampar Regency. The research time begish a week after the proposal seminar until dagree seminar. Data collection tecnhiques used a tecniqhues of observation, interviews, documentation and literarur. The Result of this stady indicate that this tradition has existed saince hundreds of years ago, has a certain customary rules and sanctions, and this tradition has several stages starting from the stage before the implementation of Ma`awuo, the implementation of the event ma`awuo, until the stages after the event Ma`awuo.Key word : Tradition, Ma`awuo Bakuok Lake